2016
DOI: 10.1002/1873-3468.12071
|View full text |Cite
|
Sign up to set email alerts
|

F‐box protein FBXL2 inhibits gastric cancer proliferation by ubiquitin‐mediated degradation of forkhead box M1

Abstract: Edited by Kazuhiro IwaiF-box/LRR-repeat protein 2 (FBXL2), a component of Skp-Cullin-F box (SCF) ubiquitin E3 ligase, has been shown to inhibit tumorigenesis by targeting and ubiquitinating several oncoproteins. However, its role in gastric cancer remains poorly understood. Here, by tandem mass spectrometry, we show that FBXL2 interacts with forkhead box M1 (FoxM1) transcription factor. As a result, FBXL2 promotes ubiquitination and degradation of FoxM1 in gastric cancer cells. Furthermore, overexpression of F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…It also inhibited leukemic cell proliferation by targeting cyclin D2 (31). FBXL2 also decreased gastric cancer proliferation by promoting degradation of forkhead box M1 (32).…”
Section: Discussionmentioning
confidence: 96%
“…It also inhibited leukemic cell proliferation by targeting cyclin D2 (31). FBXL2 also decreased gastric cancer proliferation by promoting degradation of forkhead box M1 (32).…”
Section: Discussionmentioning
confidence: 96%
“…21 Besides, FBXL2 inhibits gastric cancer proliferation and invasion by ubiquitin-mediated degradation of forkhead box M1 (FoxM1) transcription factor in gastric cancer cells. 22 Chen et al reported that FBXL2 is ectopically expressed in a transformed murine lung epithelial (MLE) cell line. Ectopic expression of FBXL2 induces cyclin D2 degradation, whereas knockdown of FBXL2 results in signicant increase in cyclin D2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Cdh1 stimulated degradation of FoxM1 protein in HeLa 49 , U2OS 17 , and MCF-7 cells 50 . Moreover, Fbxl2 (a component of Skp-Cullin-F box ubiquitin E3 ligase) 51 and VprBP (a component of cullin 4-based E3 ubiquitin ligase) 52 have been reported to regulate the degradation of FoxM1 in different cells. Here we discovered that FoxM1 directly interacted with Cdh1, rather than the adaptor Cdc20.…”
Section: Discussionmentioning
confidence: 99%